2014
DOI: 10.1016/j.jjcc.2013.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Rationale and design of J-ACCESS 4: Prognostic impact of reducing myocardial ischemia identified using ECG-gated myocardial perfusion SPECT in Japanese patients with coronary artery disease

Abstract: The multicenter, prospective cohort J-ACCESS 4 study aims to clarify the prognostic impact of reducing myocardial ischemia determined using electrocardiogram-gated MPS in Japanese patients with coronary artery disease. We started to register patients in J-ACCESS 4 at 74 facilities during June 2012 and will continue to do so until December 2013 or until the cohort comprises 500 patients who will participate in the study from one month before, until two months after stress/rest MPS assessment. Imaging data, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…Coronary revascularization will be the primary indication to improve chest symptoms and the prognosis of patients with moderate to severe myocardial ischemia [6]. J-ACCESS 4 study is in progress to assess the prognostic impact of reducing myocardial ischemia identified using ECG-gated myocardial perfusion SPECT [7]. In the present study, we identified high cardiac risk even without ischemia, and this was usually due to complications with DM and chronic kidney disease (CKD) as well as reduced LV contractility.…”
Section: Discussionmentioning
confidence: 81%
“…Coronary revascularization will be the primary indication to improve chest symptoms and the prognosis of patients with moderate to severe myocardial ischemia [6]. J-ACCESS 4 study is in progress to assess the prognostic impact of reducing myocardial ischemia identified using ECG-gated myocardial perfusion SPECT [7]. In the present study, we identified high cardiac risk even without ischemia, and this was usually due to complications with DM and chronic kidney disease (CKD) as well as reduced LV contractility.…”
Section: Discussionmentioning
confidence: 81%
“…The Organizing Committee of the Japanese Assessment of Cardiac Events and Survival Study by Quantitative Gated SPECT (J-ACCESS) 4 planned this multicenter, prospective cohort study. The rationale and design of the J-ACCESS 4 study is described elsewhere [9]. During the registration period between June 1, 2012 and December 30, 2013, 494 patients at 59 institutions who met the inclusion criteria were enrolled in the study one month before, until two months after a first stress/rest MPI.…”
Section: Study Design and Participantsmentioning
confidence: 99%
“…All reconstructed short-axis data created at each site were sent to the J-ACCESS site (Osaka, Japan) in Digital Imaging and Communication in Medicine (DICOM) format. An image interpretation committee evaluated digital images in a blinded manner to increase scoring objectivity as described [9]. Summed stress (SSS), summed rest (SRS) and summed difference (SDS) scores were converted into ratios (%) of the total myocardium (%myo stress, %myo rest, and %myo ischemia, respectively).…”
Section: Evaluation Of Mpi Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, ischemic reduction observed on SPECT images was greater with PCI plus optimal medical therapy than with optimal medical therapy alone. In Japan, the J-ACCESS IV trial [36], which is similar to the design of the COURAGE Trial Nuclear Substudy, has been started in order to collect data prospectively. Prior to that, we conducted a retrospective pilot study to investigate a relationship between the ischemic reduction and the onset of cardiac events after treatment in Japanese patients with CAD.…”
Section: Decision Of Therapeutic Strategy For Cad On the Basis Of Iscmentioning
confidence: 99%